Demand constraints on agricultural growth in East and Southern Africa: A General Equilibrium Analysis - Diao, Xinshen; Dorosh, Paul A. (Wiley, 2007)
This article analyses demand constraints on agricultural growth in seven countries of East and Southern Africa using an applied general equilibrium framework. It finds that both traditional and non-traditional export crops have limited potential to raise incomes because of demand constraints (for traditional exports) or a relatively small base (for non-traditional exports).The best prospects for agriculture-led growth remain in the food sector, where domestic demand represents a large and growing market. Improvements in market efficiency and simultaneous growth in the livestock sectors can help spur demand further and avert falls in prices. Achieving rapid gains in farm incomes, however, also requires investment in rural infrastructure to reduce marketing costs, and demand-enhancing growth in the non-agricultural sector to spur demand.